The Influence of Literacy and Numeracy on Problem-Solving Ability in Mathematics Learning - Fitriani; Yasir Arafat; Faipri Selegi, Susanti; Makroni, Golaleh; Pratama, Aldora (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to examine the effect of numeracy-based learning on elementary school students' mathematical problem-solving skills, particularly in the subject of flat shapes in the fourth grade at SD Negeri 33 Palembang. The urgency of this study is based on the importance of strengthening students' numeracy skills as part of the National Literacy Movement, which emphasizes analytical thinking and logical reasoning in mathematics learning. This study used a quantitative approach with a True Experimental Design of the Nonequivalent Control Group Design type. The research subjects consisted of 40 students divided into two classes, namely the IVC experimental class and the IVD control class. Both the experimental and control classes had 20 students each. Data collection techniques were carried out through a multiple-choice test consisting of 10 questions and documentation, while data analysis used the Independent Sample t-test. The results showed a significant effect of numeracy literacy learning on students' mathematical problem-solving abilities, which had an impact on improving conceptual understanding and cognitive engagement in learning mathematics.